Characterization of ech-42, a Trichoderma harzianum endochitinase gene expressed during mycoparasitism. - Carsolio, C (1994)
A gene (ech-42; previously named ThEn-42) coding for one of the endochitinases produced by the biocontrol agent Trichoderma harzianum IMI206040 was cloned and characterized. Expression of the cDNA clone in Escherichia coli resulted in bacteria with chitinase activity. This chitinase has been shown to have lytic activity on Botrytis cinerea cell walls in vitro. The ech-42 gene was assigned to a double chromosomal band (chromosome V or VI) upon electrophoretic separation and Southern analysis of the chromosomes. Primer extension analysis indicated that transcription of the gene begins preferentially 109 bp upstream of the translation initiation codon. Expression of ech-42 was strongly enhanced during direct interaction of the mycoparasite with a phytopathogenic fungus when confronted in vitro and by growing it in minimal medium containing chitin as sole carbon source. Similarly, light-induced sporulation resulted in high levels of transcript, suggesting developmental regulation of the gene. The implications of these findings are discussed.